N Pendampingan Kelompok Pemuda dalam Penyusunan Paket Wisata Desa Bongan, Tabanan, Bali - Lumanauw, Nelsye; Ari Agustini, I Gusti Ayu (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2024)
Community service by Politeknik Internasional Bali team was carried out from April to September 2023 for the Bongan Village youth group with an average age of 25 to 30 years. The program was a continuation of previous activities in 2022 which were participated by tourist village managers with an average age of 40 to 50 years. The team considers that village youth play an important role in developing the village through tourism packages that can be offered to tourists. In facts, the team found that not all young people who took part in the mentoring knew about their tourism potential in the village. Through mentoring programs, village youth become more concerned about the surrounding environment and could develop existing tourism potential into attractive tour packages for tourists. The methods used are the preparation, training and mentoring stages. The output of the assistance is a tour package brochure which is expected to increase the diversity of existing tour packages to attract tourist visits to Bongan Village.